Antioxidant and hepatoprotective property of squalene for counteracting the oxidative damage induced by methotrex- ate in experimental rats - Sumi, Edakkukaran Sudhakaran; Dara, Pavan Kumar; Mannuthy, Rosemol Jacob; Ganesan, Balaraman; Anandan, Rangasamy; Mathew, Suseela (Acta Biologica Szegediensis, 2021)
Methotrexate (MTX), an antifolate drug, is extensively prescribed for patients suﬀering from diseases like cancer, psoriasis, neoplasms, and rheumatoid arthritis. Despite its eﬀectiveness, MTX sometimes ﬁnds limited application because its undesirable side eﬀects, including hepatic or renal impairment, bone marrow toxicity and gastrointestinal mucosal injury. Squalene, a highly unsaturated isoprenoid compound, isolated from shark liver oil has great potential in neutralizing the damaging eﬀects triggered by free radicals. Therefore, in this study, the protective role of dietary squalene supplementation on oxidative stress induced by methotrexate in experimental rats was evaluated. A signiﬁcant reduction was displayed in the activities of catalase (CAT) and superoxide dismutase (SOD) in MTX-intoxicated groups compared to other groups. Similarly, the activities of glutathione dependant enzymes (GPx and GST) and reduced glutathione (GSH) in MTX-induced groups were shown to be lower compared to the untreated control. Increased LPO (lipid peroxide) level was found in MTX-intoxicated groups compared to other groups. In addition, alterations in the levels of liver marker enzymes like AST, ALP, ALT, and LDH were noticed in MTX intoxicated groups compared to other groups. Biochemical results were conﬁrmed by the histopathological examination of liver sections. In conclusion, the result obtained in the present study proposes that squalene exerts antioxidant activity and is capable of ameliorating oxidative stress and liver injury induced by MTX.